Practical measurement of the energy resolution for meV‐resolved inelastic X‐ray scattering. (9th April 2021) - Ishikawa, Daisuke; Baron, Alfred Q. R.
Abstract : Several different methods of measuring the energy resolution for meV‐resolved inelastic X‐ray scattering are investigated. Quantitative determination of inelastic contributions to the scattering from plexiglass and borosilicate glass enables an efficient, single scan, approach to resolution determination for a large (4 × 7) array of analyzers. Abstract : Several different ways of measuring the energy resolution for meV‐resolved inelastic X‐ray scattering (IXS) are compared: using scattering from poly(methyl methacrylate), PMMA, using scattering from borosilicate glass (Tempax), and using powder diffraction from aluminium. All of these methods provide a reasonable first approximation to the energy resolution, but, also, in all cases, inelastic contributions appear over some range of energy transfers. Over a range of ±15 meV energy transfer there is good agreement between the measurements of PMMA and Tempax at low temperature, and room‐temperature powder diffraction from aluminium, so we consider this to be a good indication of the true resolution of our ∼1.3 meV spectrometer. The resolution over a wider energy range is self‐consistently determined using the temperature, momentum and sample dependence of the measured response. The inelastic contributions from the PMMA and Tempax, and their dependence on momentum transfer and temperature, are then quantitatively investigated. The resulting data allow us to determine the resolution of our multi‐analyzer array efficiently using a single scan. The importance of this procedure is demonstrated by showing that the results of the analysis of a spectrum from a glass are changed by using the properly deconvolved resolution function. The impact of radiation damage on the scattering from PMMA and Tempax is also discussed.